Reputation of the Natural Heritage: the Iguaçu National Park (Brazil) on the Tripadvisor Website - Albach, Valéria de Meira; Carvalho, Kemmely Guedes de; Moreira, Jasmine Cardozo (Anais Brasileiros de Estudos Turísticos, 2022)
Brazilian and international studies about online reputation continue bringing contributions to the management of attractions, equipment and tourist destinations. This research, descriptive with systematic literature review, aims to assess the opinion of users of the TripAdvisor, through a specific methodology, with the objective to recognize the online reputation of the World Natural Heritage – Iguaçu National Park. A total of 957 posts were analyzed, they positively evaluated the attraction with a maximum score of 90%. The comments were classified by keywords and then classified into 3 (three) main categories: landscape; services in the conservation unit and activities. After that, each post was classified in different aspects that resulted in 3,422 comments, 90.18% positive and 9.82% negative. The positive highlight was given to the aspects: Scenic Beauty, Landscape Landmarks, Infrastructure/Accessibility, Activities and Attractions. Negative comments, even in smaller numbers, were emphasized, as they are more complex to manage. The fact that the Park is a World Natural Heritage Site was not evidenced by the users. With this data, the PNI managers have an additional tool to assist in the management of public use, improving the services and activities carried out.